Respuesta :

Answer:  [tex]y(x) = \sqrt{\frac{7x^{14}}{-2x^7+9}}\\\\[/tex]

==========================================================

Explanation:

The given differential equation (DE) is

[tex]y'-\frac{7}{x}y = \frac{y^3}{x^8}\\\\[/tex]

Which is the same as

[tex]y'-\frac{7}{x}y = \frac{1}{x^8}y^3\\\\[/tex]

This 2nd DE is in the form [tex]y' + P(x)y = Q(x)y^n[/tex]

where

[tex]P(x) = -\frac{7}{x}\\\\Q(x) = \frac{1}{x^8}\\\\n = 3[/tex]

As the instructions state, we'll use the substitution [tex]u = y^{1-n}[/tex]

We specifically use [tex]u = y^{1-n} = y^{1-3} = y^{-2}[/tex]

-----------------

After making the substitution, we'll end up with this form

[tex]\frac{du}{dx} + (1-n)P(x)u = (1-n)Q(x)\\\\[/tex]

Plugging in the items mentioned, we get:

[tex]\frac{du}{dx} + (1-n)P(x)u = (1-n)Q(x)\\\\\frac{du}{dx} + (1-3)*\frac{-7}{x}u = (1-3)\frac{1}{x^8}\\\\\frac{du}{dx} + \frac{14}{x}u = -\frac{2}{x^8}\\\\[/tex]

We can see that we have a new P(x) and Q(x)

[tex]P(x) = \frac{14}{x}\\\\Q(x) = -\frac{2}{x^8}[/tex]

-------------------

To solve the linear DE [tex]\frac{du}{dx} + \frac{14}{x}u = -\frac{2}{x^8}\\\\[/tex], we'll need the integrating factor which I'll call m

[tex]m(x) = e^{\int P(x) dx} = e^{\int \frac{14}{x}dx} = e^{14\ln(x)}[/tex]

[tex]m(x) = e^{\ln(x^{14})} = x^{14}[/tex]

We will multiply both sides of the linear DE by this m(x) integrating factor to help with further integration down the road.

[tex]\frac{du}{dx} + \frac{14}{x}u = -\frac{2}{x^8}\\\\m(x)*\left(\frac{du}{dx} + \frac{14}{x}u\right) = m(x)*\left(-\frac{2}{x^8}\right)\\\\x^{14}*\frac{du}{dx} + x^{14}*\frac{14}{x}u = x^{14}*\left(-\frac{2}{x^8}\right)\\\\x^{14}*\frac{du}{dx} + 14x^{13}*u = -2x^6\\\\\left(x^{14}*u\right)' = -2x^6\\\\[/tex]

It might help to think of the product rule being done in reverse.

Now we can integrate both sides to solve for u

[tex]\left(x^{14}*u\right)' = -2x^6\\\\\displaystyle \int\left(x^{14}*u\right)'dx = \int -2x^6 dx\\\\\displaystyle x^{14}*u = \frac{-2x^7}{7}+C\\\\\displaystyle u = x^{-14}*\left(\frac{-2x^7}{7}+C\right)\\\\\displaystyle u = x^{-14}*\frac{-2x^7}{7}+Cx^{-14}\\\\\displaystyle u = \frac{-2x^{-7}}{7}+Cx^{-14}\\\\[/tex]

[tex]u = \frac{-2}{7x^7} + \frac{C}{x^{14}}\\\\u = \frac{-2}{7x^7}*\frac{x^7}{x^7} + \frac{C}{x^{14}}*\frac{7}{7}\\\\u = \frac{-2x^7}{7x^{14}} + \frac{7C}{7x^{14}}\\\\u = \frac{-2x^7+7C}{7x^{14}}\\\\[/tex]

Unfortunately, this isn't the last step. We still need to find y.

Recall that we found [tex]u = y^{-2}\\\\[/tex]

So,

[tex]u = \frac{-2x^7+7C}{7x^{14}}\\\\y^{-2} = \frac{-2x^7+7C}{7x^{14}}\\\\y^{2} = \frac{7x^{14}}{-2x^7+7C}[/tex]

We're told that y(1) = 1. This means plugging x = 1 leads to the output y = 1. So the RHS of the last equation should lead to 1. We'll plug x = 1 into that RHS, set the result equal to 1 and solve for C

[tex]\frac{7*1^{14}}{-2*1^7+7C} = 1\\\\\frac{7}{-2+7C} = 1\\\\7 = -2+7C\\\\7+2 = 7C\\\\7C = 9\\\\C = \frac{9}{7}[/tex]

So,

[tex]y^{2} = \frac{7x^{14}}{-2x^7+7C}\\\\y^{2} = \frac{7x^{14}}{-2x^7+7*\frac{9}{7}}\\\\y^{2} = \frac{7x^{14}}{-2x^7+9}\\\\y = \sqrt{\frac{7x^{14}}{-2x^7+9}}\\\\[/tex]

We go with the positive version of the root because y(1) is positive, which must mean y(x) is positive for all x in the domain.

ACCESS MORE
EDU ACCESS
Universidad de Mexico